ADAPTIVE OPTIONS OF SOFT WINTER WHEAT CULTIVARS ON A TRAIT ‘MASS (WEIGHT) OF 1000 SEEDS’ UNDER CONDITIONS OF PROVOCATIVE BACKGROUND (‘ZASUSHNIK’) - N. S. Kravchenko; E. V. Ionova (Зерновое хозяйство России, 2018)
The parameters of ecological plasticity and stability of the trait ‘mass of 1000 seeds’ of soft winter wheat cultivars under conditions of provocative background (‘zasushnik’) have been considered in the paper. Stress tolerance, genetic versatility and homeostasis of the trait have been studied as well. During the study the cultivar ‘Don’ and ‘Spartak’ showed a low coefficient of variability of the trait, V=20,3% and V=20,1% respectively. All cultivars’ coefficient of line regression (bi) was determined which is more than one, indicating that mass of 1000 seeds tends to increase at better growing conditions. The cultivars ‘Don 95’, ‘Don 107’, ‘Lidiya’, ‘Marafon’, ‘Don 107’, ‘Don 95’ and ‘Don 93’ showed ecological stability of the trait ‘mass of 1000 seeds’. During the study the cultivars ‘Lidiya’, ‘Don 107’, ‘Don 95’ and ‘Don 93’ showed the highest stress tolerance. The cultivars ‘Don 93’ and ‘Spartak’ showed stability of the trait ‘mass of 1000 seeds’ when the growing conditions changed.